Utilizing the arts to improve health, resilience, and well-being (HeRe We Arts®): a randomized controlled trial in community-dwelling individuals with chronic medical conditions - Gallagher, Lisa; Shella, Tamara; Bates, Debbie; Briskin, Isaac; Jukic, Maria; Bethoux, Francois (Frontiers in Public Health, 2024)
Background Healthcare workers are concerned with promoting behavior changes that enhance patients’ health, wellness, coping skills, and well-being and lead to improved public health. The purpose of this randomized controlled trial was to determine if participation in an 8-week arts-based program leads to improved mood, health, resilience, and well-being in individuals with chronic health conditions as compared to a wait list control group. Methods Self-report questionnaires for well-being, mental health, physical health, overall health, social health, mood, coping, and resilience were administered at baseline, Week 8 (end of program), and Week 16 (8-week follow-up). Results Statistically significant improvements were noted in all outcome measures for the treatment group, as well as in most areas compared to the control group. Many of the positive results at Week 8 were either maintained or further improved at Week 16. Discussion These results suggest that arts-based programming can have a positive effect on the mood, health, resilience, and well-being of individuals with chronic health conditions. Therefore, arts-based programming should be utilized more frequently in the management of chronic conditions in community-dwelling individuals. These benefits should be further assessed in larger clinical trials.